Waqfnomic Based on Muna Culture as an Alternative Model of Islamic Philanthropy - Insawan, Husain; Alwahidin, Alwahidin; Rahman, Muljibir; Sahlan, Sahlan; Putri, Azzahrah Insawan (KARSA Journal of Social and Islamic Culture, 2024)
The potential for Waqf in Indonesia is huge, as in the case of Muna Regency. This research explains the problems of Waqf in the Muna cultural approach. The aim is to analyze the problems of waqf institutions in a religious and cultural context. The research method used is qualitative, and it looks at the unique cultural paradigm in waqf land management. This research source uses primary data by conducting interviews with the main actors of Waqf, traditional leaders, religious leaders, and leaders of religious institutions. Secondarily, data is obtained from sources or other supporting parties related to the research object, such as reference books, monographs, proceedings, research reports, and journals. The researcher offers a Waqfnomic Model, namely Economic-Cultural Waqf or culture-based Waqf, whose implementation involves traditional and religious leaders and can be displayed online using information technology, making it more millennial, simple, and easy to access. Access is right on target and legally friendly.